A patient and family reporting system for perceived ambulatory note mistakes: experience at 3 U.S. healthcare centers. (3rd September 2019) - Bourgeois, Fabienne C; Fossa, Alan; Gerard, Macda; Davis, Marion E; Taylor, Yhenneko J; Connor, Crystal D; Vaden, Tracela; McWilliams, Andrew; Spencer, Melanie D; Folcarelli, Patricia; Bell, Sigall K
Abstract: Objective: The study sought to test a patient and family online reporting system for perceived ambulatory visit note inaccuracies. Materials and Methods: We implemented a patient and family electronic reporting system at 3 U.S. healthcare centers: a northeast urban academic adult medical center (AD), a northeast urban academic pediatric medical center (PED), and a southeast nonprofit hospital network (NET). Patients and families reported potential documentation inaccuracies after reading primary care and subspecialty visit notes. Results were characterized using descriptive statistics and coded for clinical relevance. Results: We received 1440 patient and family reports (780 AD, 402 PED, and 258 NET), and 27% of the reports identified a potential inaccuracy (25% AD, 35% PED, 28% NET). Among these, patients and families indicated that the potential inaccuracy was important or very important in 58% of reports (55% AD, 55% PED, 71% NET). The most common types of potential inaccuracies included description of symptoms (21%), past medical problems (21%), medications (18%), and important information that was missing (15%). Most patient- and family-reported inaccuracies resulted in a change to care or to the medical record (55% AD, 67% PED, data not available at NET). Discussion: About one-quarter of patients and families using an online reporting system identified potential documentation inaccuracies in visit notes and more than half were considered important by patients and clinicians, underscoring the potential role of patients and families as ambulatory safety partners. Conclusions: Partnering with patients and families to obtain reports on inaccuracies in visit notes may contribute to safer care. Mechanisms to encourage greater use of patient and family reporting systems are needed.